Chromosome dynamics and spindle microtubule establishment in mouse embryos. Issue 6 (23rd April 2020) - Macaulay, Angus D.; Allais, Adélaïde; FitzHarris, Greg
Abstract: Chromosome segregation errors in mammalian embryos are common and jeopardize embryo health. Here, we perform for the first time 4‐Dimensional imaging and tracking of chromosomes and centromeres through each preimplantation mitotic cell division in mouse embryos to define the normal dynamics of chromosome segregation. We show that a microtubule (MT)‐dependent inward movement of chromosomes occurs at the time of nuclear envelope breakdown (NEBD), particularly in the earliest cell divisions, to position chromosomes prior to spindle assembly. Establishment of a rudimentary metaphase plate occurs immediately after NEBD, and is followed by a progressive alignment and biorientation of mitotic chromosomes. Stable end‐on kinetochore‐MT attachments form rapidly and attachment errors are uncommon. Altogether our data describe a rapid and efficient spindle assembly pathway that apparently minimizes the need for canonical MT attachment error correction in normally dividing embryos.